Publications of Rev. Professor Joseph Życiński from the years 1999-2011 - Adamczyk, Tomasz (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2011)
List of publications of Rev. Professor Joseph Życiński written since 1999.